A Study into Students’ Views on Guided Peer Feedback in Group Work - Xie, Jingjing; Mu, Fengying (Chinese journal of applied linguistics, 2015)
Peer feedback is a key to the quality of group work in foreign language classrooms. In order to better understand the use of peer feedback in spoken English, a ten-week study was conducted by combining peer feedback with group work. Based on Scaffolding Instruction of Constructivism, this study chose three different tools – a checklist, a qualitative feedback sheet and a grading sheet, to guide peer feedback. A questionnaire survey and three interviews were adopted to investigate the students’ views and attitude toward guided peer feedback. We found: (1) Guided peer feedback plays a positive role in improving the quality of group work and its three forms were positively received by the participants; (2) Among the three tools – the checklist, the qualitative feedback sheet and the grading sheet, the grading sheet was most welcomed; (3) Only by designing the appropriate peer feedback forms and the tasks at the same time, could peer feedback achieve good results.